Fluorescence and colorimetric dual-mode sensor for visual detection of malathion in cabbage based on carbon quantum dots and gold nanoparticles. (1st May 2021) - Liang, Nini; Hu, Xuetao; Li, Wenting; Mwakosya, Anjelina W.; Guo, Ziang; Xu, Yiwei; Huang, Xiaowei; Li, Zhihua; Zhang, Xinai; Zou, Xiaobo; Shi, Jiyong
Highlights: CQDs and GNPs were synthesized as fluorescence and colorimetric nanomaterials, respectively. CQDs-GNPs-based dual-mode nanosensor was applied for malathion detection. Standard arrays were fabricated by a smartphone and used for visual detection of malathion. Cabbages adulterated by malathion were detected by the established calibration curves and standard arrays. Abstract: A dual-mode fluorescence/colorimetric sensor based on carbon quantum dots (CQDs) and gold nanoparticles (GNPs) was developed for visual detection of malathion in cabbage. The CQDs-GNPs nanocomposite exhibited emission wavelength at 527 nm and absorption wavelength at 524 nm. The fluorescence intensity increased and absorption decreased with addition of malathion. Fluorescence and colorimetric calibration curves were established based on fluorescence intensity (R 2  = 0.9914) and absorbance (R 2  = 0.9608) in the range of 1 × 10 −9 –1 × 10 −2 M, respectively. Furthermore, fluorescence and colorimetric standard arrays were prepared for visual detection of malathion according to the change of fluorescence brightness and color. Finally, the approximate concentrations of malathion in cabbage samples were estimated by the standard arrays and naked eyes. The calibration curves were used for accurate detection in cabbage samples with recoveries of 89.9%–103.4% (fluorescence) and 88.7%–107.6% (colorimetric). The established sensor for visual malathion detection in cabbage was accurate with strong application potential, especially for rapid screening.